Organizational Communication Model for Local Government Agencies Implementing the Foster Parent Movement to Prevent Stunting (Genting) - Veny Malida; Abdul Firman Ashaf (LPPM STIAB JINARAKKHITA LAMPUNG, 2026)
Stunting remains a major public health challenge that requires effective collaboration among government institutions, the private sector, and communities. To strengthen stunting prevention, the Indonesian government introduced the Foster Parent Movement for Stunting Prevention (Genting), which encourages cross-sector stakeholder participation in supporting families at risk of stunting. This study aims to analyze the organizational communication model employed by local government agencies in implementing the Genting Program in Pringsewu Regency. This study adopted a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving five key informants, including Family Planning Counselors, local government officials, sub-district and village representatives, and program stakeholders. Data were analyzed using an interactive qualitative analysis model. The findings indicate that the implementation of the Genting Program relies on both formal and informal communication operating vertically and horizontally across organizational levels. Family Planning Counselors act as key communicators linking local government agencies, village administrations, private-sector partners, and communities. Informal communication proved more effective than formal coordination in fostering mutual understanding, building trust, and encouraging stakeholder participation as foster parents. However, communication barriers remain due to different perceptions regarding funding responsibilities and forms of stakeholder involvement. This study contributes to organizational communication literature by demonstrating that informal communication functions as an adaptive feedback mechanism that strengthens inter-organizational collaboration, thereby extending Katz and Kahn's Open Systems Theory. The findings also provide practical recommendations for integrating formal coordination with interpersonal communication strategies to enhance stakeholder engagement and improve local stunting prevention programs.